Four Basic Functions of Cooperatives. Their Current Status - odelso Schneider, José (Cooperativismo & Desarrollo, 2013)
Cooperative organizations and solidarity enterprises contribute to generate an economy that generates life, justice and participation. Besides generating goods and services to meet the basic needs of its members, projects tend to be, at the same time excellent schools for learning administrative, economic, democratic and social complexities. They promote a service economy rather than a profit economy and therefore its results are irradiated and they are distributed equally among the partners, opposing capitalist processes of concentration / exclusion from power, property, income and knowledge. We intend to present this study from a hermeneutic, doctrinal and epistemological perspective addressing the four major functions of the cooperative society and present economy: democracy, citizenship, social cohesion and the economy of life.